2016
DOI: 10.1371/journal.pone.0168794
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Profiling of the Human Retina: Comparison with Other Ocular Structures, Brain and Plasma Reveals Tissue Specificities

Abstract: Gangliosides make a wide family of glycosphingolipids, highly heterogeneous in both the ceramide moiety and the oligosaccharide chain. While ubiquitously expressed in mammalian tissues, they are particularly abundant in the brain and the peripheral nervous system. Gangliosides are known to play a crucial role in the development, maintenance and functional integrity of the nervous system. However, the expression and roles of gangliosides in the retina, although often considered as a window on the brain, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…In addition, a later study also found significant depletion of multiple bi-GlcNAc core 2 and I-branched structures 37 . Also consistent with the decrease in bi-GlcNAc core-2 structures in gastric cancer, low expression of B3GNT3 in stomach cancer is significantly associated with decreased overall survival 38 . B3GNT3 is necessary for adding the second GlcNac to core 2 structure 39 and therefore upstream of all significantly depleted structures (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, a later study also found significant depletion of multiple bi-GlcNAc core 2 and I-branched structures 37 . Also consistent with the decrease in bi-GlcNAc core-2 structures in gastric cancer, low expression of B3GNT3 in stomach cancer is significantly associated with decreased overall survival 38 . B3GNT3 is necessary for adding the second GlcNac to core 2 structure 39 and therefore upstream of all significantly depleted structures (Fig.…”
Section: Resultssupporting
confidence: 70%
“…To explore the broad applicability of GlyCompare, we used our method to calculate substructure abundance for mucin-type O-glycans 37 (Fig. 7 ), glycolipids 38 (Supplementary Fig. 12 ), and site-specific compositional N-glycosylation 22 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plant GIPCs are structurally homologous to the animal gangliosides that are absent in plants. Gangliosides are acidic glycolipids containing sialic acid in their polar head that play an important role in immunity, signal transduction in the PM that essential for brain, and retinal functions in animal cells ( 68 , 69 ). It is possible that polyglycosylated GIPCs have a similar role to gangliosides.…”
Section: Discussionmentioning
confidence: 99%
“…Plant GIPCs are structurally homologous to the animal gangliosides that are absent in plants. Gangliosides are acidic glycolipids containing sialic acid in their polar head that play an important role in immunity, signal transduction in the PM that essential for brain and retinal functions in animal cells (Sonnino & Prinetti, 2010) (Sibille et al, 2016). It is possible that polyglycosylated GIPCs have a similar role to gangliosides.…”
Section: Gipc Structure In Membrane Organizationmentioning
confidence: 99%